1993
DOI: 10.1105/tpc.5.8.831
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative Mutants of Opaque2 Suppress Transactivation of a 22-kD Zein Promoter by Opaque2 in Maize Endosperm Cells.

Abstract: In maize endosperm, genes encoding the 22-kD zein class of storage proteins are regulated by the OPAQUE2 locus. The Opaque2 (02) protein shares homology with the basic domainlleucine zipper class of transcriptional activators. Using microprojectile bombardment, we have shown that 0 2 is capable of transactivating a 22-kD zein promoter in maize endosperm suspension cultures and in longitudinal sections of intact endosperm. Two mutant forms of the 02 gene were constructed by deleting regions that encode either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 50 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…This subset, identified by the M1 family of sequences, actually codes for mature zein polypeptides of 246 to 241 amino acids and explains the size variability within the heavy zein subclass that is subdivided into zH1 and zH2, respectively (Viotti et al, 1985). In vitro experiments showed that Opaque-2 binds as homodimer to the motif 5Ј-TCCACGTAGA-3Ј (O2 box) that occurs once in the promoter of the heavy chain zein genes about Ϫ300 bp from the ATG start codon (Schmidt et al, 1990) and data from in vivo experiments support this binding specificity (Unger et al, 1993). However, evidences for promiscuity in DNAmotif binding for this type of bZIP factor (Izawa et al, 1993) have been reported (Yunes et al, 1994(Yunes et al, , 1998.…”
mentioning
confidence: 71%
“…This subset, identified by the M1 family of sequences, actually codes for mature zein polypeptides of 246 to 241 amino acids and explains the size variability within the heavy zein subclass that is subdivided into zH1 and zH2, respectively (Viotti et al, 1985). In vitro experiments showed that Opaque-2 binds as homodimer to the motif 5Ј-TCCACGTAGA-3Ј (O2 box) that occurs once in the promoter of the heavy chain zein genes about Ϫ300 bp from the ATG start codon (Schmidt et al, 1990) and data from in vivo experiments support this binding specificity (Unger et al, 1993). However, evidences for promiscuity in DNAmotif binding for this type of bZIP factor (Izawa et al, 1993) have been reported (Yunes et al, 1994(Yunes et al, , 1998.…”
mentioning
confidence: 71%
“…In the case of barley, for which mutants of HvABI5 are not available, one way to study the effect of a transcription factor is through the expression of a dominant-negative form of the protein to repress the function of the wild-type gene. This has been particularly suitable for bZIP factors (Unger et al, 1993;Fukazawa et al, 2000;Sprenger-Haussels and Weisshaar, 2000). We constructed a dominant-negative form of HvABI5, and when introduced into aleurones, it efficiently repressed the ABA induction of the ABRC3-GUS reporter construct (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The moderate increase in GUS activity observed with the sense effector was that expected in a wild type endosperm expressing its physiological level of transcription factors (BLZ1 among them), where optimal (or close to optimal) concentrations of BLZ1 will be present. The five to 10 times enhancement reported with other bZIP, such as maize O2 and wheat SPA (Albani et al, 1997;Unger et al, 1993), are probably due to the use of heterologous systems such as tobacco protoplasts or cultured cell lines, where background levels of these effectors are probably different from the native tissue. The effects observed for the Blz1 antisense constructs in co-bombarded barley endosperms are of particular relevance since avoiding the synthesis of a crucial transcription factor would be expected to have dramatic effects on the expression of the gene(s) that it regulates.…”
Section: Blz1 Trans-regulates Gene Expression From Motives In Endospementioning
confidence: 99%